Laparoscopic Management for Carcinoid Metastasis to the Spleen - Balmforth, Damian (Hindawi Publishing Corporation, 2011)
We report a rare case of a laparoscopic splenectomy performed for a carcinoid metastasis. The patient represented with pleuritic left-sided chest pain from pleural deposits 9 years following resection of a primary lung carcinoid tumour. They were found to have a 4.7 cm splenic lesion on CT with a probable left acetabular metastasis demonstrated on Gallium PET scan. The patient underwent laparoscopic splenectomy for debulking treatment of the splenic lesion that was confirmed to be a splenic metastasis of the resected carcinoid lung tumour. Following an uncomplicated recovery, the patient was discharged on the second postoperative day. On discharge, she received adjuvant therapy with Lutetium 177 DOTATATE. This is the first report of a carcinoid splenic metastasis successfully treated with laparoscopic splenectomy.